2014
DOI: 10.1074/jbc.m114.602680
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Glycoprotein Modifications Regulate Colon Cancer Stem Cells and Colon Adenoma Progression in Apcmin/+ Mice through Altered Wnt Receptor Signaling

Abstract: Background: GnT-V levels are implicated in regulating cancer stem cells and tumor development. Results: GnT-V levels via altered Wnt signaling regulate the compartment of colon cancer stem cells and tumor formation. Conclusion: GnT-V levels modulate Wnt signaling that regulate colon adenoma progression. Significance: A specific post-translational modification regulates Wnt signaling and colon cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 70 publications
5
46
0
Order By: Relevance
“…Breast cancer progression and metastasis induced by a viral oncogene in transgenic mice is markedly suppressed in Mgat5-deficient background 73 . Moreover, GnT-V-mediated glycosylation regulates the colon cancer stem cell compartment and tumour progression through WNT signalling 74 .…”
Section: Sialylationmentioning
confidence: 99%
“…Breast cancer progression and metastasis induced by a viral oncogene in transgenic mice is markedly suppressed in Mgat5-deficient background 73 . Moreover, GnT-V-mediated glycosylation regulates the colon cancer stem cell compartment and tumour progression through WNT signalling 74 .…”
Section: Sialylationmentioning
confidence: 99%
“…1 Qualitative and/or quantitative deviations from “normal state” are attributes of numerous human diseases. 2 In particular, aberrations in protein N-glycosylation patterns 35 are observed due to different cancer conditions and their clinical stages. 67 These changes have been emphasized by several research groups which have demonstrated significant changes to the healthy serum glycomic profiles for a number of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have confirmed that ␤1,4GalTV could regulate the self-renewal of glioma-initiating cells (19). N-acetylglucosaminyltransferase V promotes the self-renewal and tumorigenicity of colon cancer stem cells (20). The N-glycan inhibitor tunicamycin inhibits the self-renewal ability and tumorigenesis of glioma stem-like cells (21).…”
mentioning
confidence: 76%